Validity and Reliability of the Indonesian Version Gross Motor Function Measure to Measure Gross Motor Function in Cerebral Palsy Children - Selly C Anggoro; Amendi Nasution; Luh K Wahyuni; Aria Kekalih (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives: Cerebral palsy (CP) is the most physical disabling disease in children. Gross motor capacity in CP usually measured and evaluated by Gross Motor Function Measure (GMFM), a standardizedobservational instrument to evaluate gross motor function. Studies showed GMFM reliable, valid, and responsive to change of CP gross motor function. This research aims to examine validity and reliabilityof GMFM translated into Indonesian.Methods: Cross sectional study with consecutive sampling of CP children aged 2-15 years came to pediatric rehabilitation clinic at RSCM Medical Rehabilitation Department or YPAC Jakarta. Subjects classified by age, type, anatomical distribution, and severity.Gross motor function evaluated with 88 GMFM items translated into Indonesia. Inter-rater evaluated gross motor function through video records. Criterion validity tested by correlation coefficient, construct validity tested by comparing GMFM item with dimension total scores and GMFM total score with corrected Spearman correlation. Inter-rater reliability tested by unpaired T-test, internal consistency by alpha Cronbach.Results: Thirty one CP children with mean age 7 years 11 months, mean GMFM score 58.40 (SD=49.09).No significant difference of all GMFM dimensions; almost all GMFM items obtained from inter-rater evaluation. Good internal consistency (alpha Cronbach 0.884) and good criterion validity of all dimensions;; inter-item and total correlations good to strong (r=0.523-0.859).Conclusion: GMFM Indonesian has good to strong criterion validity. Construct validity of all dimensions was quite good. Internal consistency was good. No significant difference between inter-raters showed GMFM inter-rater reliability good enough.Keywords: Cerebral palsy, gross motor function, gross motor function measure, validity, reliability.